I bolli dell’OctPro-OctSal Group. Riflessioni sulla circolazione urbana a partire dai recenti scavi nell’area degli Horti Lamiani (Esquilino, Roma) - Cardarelli, Viviana (Rei Cretariae Romanae Fautorum Acta, 2022)
This paper focuses on the OctPro-OctSal Group of stamps produced in Central Italy between the Flavian period and the 2nd century AD. These stamps have been identify in several deposits of the newly excavated contexts from the Horti Lamiani area (Rome) and dated from the 2nd century AD to Late Antiquity (4-5th century AD). By exploiting these examples, we will reconsider the main features of the stamps and their role in the urban economy. Our analysis of the identified group has revealed the presence of both low- and high-quality examples, as well as new stamps. Analysis also revealed that Consp. 37.5 commonly stamped by the potters of the OctPro-OctSal Group is characterised by multiple rim shapes and was still produced during the 2nd century AD, an observation which is supported by the high number of those cups in the early 3rd century deposits of the Horti Lamiani. The data collected from these assemblages, in addition to other deposits discovered in Rome, suggest that the Italian Sigillata continue to be produced into until the last decades of the 2nd century and in the light of the above considerations, it seems possible to reject the presence of a chronological gap between the activity of the Sigillata Italica figlinae and the workshops of the Central Tiber Valley Red Slip Ware.